"Stout Women Can Now Be Stylish": Stout Women's Fashions, 1910–1919. (3rd July 2017) - Keist, Carmen
Abstract : Prior to the turn of the twentieth century, women had limited access to ready-to-wear clothing. As the women's ready-to-wear industry developed in the 1890s, "average-sized" women could easily purchase clothing, but was this the same for women considered stout? Larger women, referred to as stout during the 1910s, comprised approximately 12.7 percent of the US population. The term "stout" indicated a figure (often of matronly appearance) with generous bust, back, and hip curves that decidedly did not fit in with fashion's demands for the slim figure. To explore attitudes surrounding the stout woman and the development of full-figured fashions, the author took a historical method approach using primary sources from theNew York Times, Vogue, andGood Housekeeping . This study identified and analyzed the introduction and emergence of stout women's ready-to-wear clothing, separate retail departments for different-sized clothing, and design details recommended to enhance and hide the figure.